Proenkephalin (PENK) as a Novel Biomarker for Kidney Function. (1st November 2017) - Beunders, Remi; Struck, Joachim; Wu, Alan H B; Zarbock, Alexander; Di Somma, Salvatore; Mehta, Ravindra L; Koyner, Jay L; Nadim, Mitra K; Maisel, Alan S; Murray, Patrick T; Neath, Sean-Xavier; Jaffe, Allan; et al.
Abstract: Background: The assessment of kidney function and detection of acute kidney injury (AKI) remain cumbersome. On the one hand, because of limited accuracy of established tests: The most widely used methods are creatinine based, which lack in sensitivity, as creatinine is not purely filtrated by the kidney and rises relatively late after onset of AKI. On the other hand, because of labor-intensiveness: Gold standard inulin clearance and comparable methods involve intravenous compound infusion, blood sampling at several time points, and have error-sensitive determination methods. In recent years, several biomarkers have been put forward (e.g., NGAL, KIM-1, TIMP-2*IGFBP-7), but clinical implementation is limited up to now. Content: Proenkephalin (PENK) represents a new candidate to determine kidney function. This peptide is cleaved from the precursor peptide preproenkephalin A alongside enkephalins (endogenous opioids) and is filtrated in the glomerulus. PENK plasma concentration appears to accurately represent glomerular filtration rate in patients diagnosed with sepsis or cardiac diseases. Moreover, increased PENK concentration is found to be associated with longer-term outcome concerning AKI and cardiac diseases. Lastly, the predominant receptor of enkephalins, the δ-opioid receptor, is expressed with the highest density in the kidney, suggesting that enkephalins could also exert a direct effect on kidney function. Summary: In this review, we present an overview of enkephalins and the assessment of kidney function using this possible new functional biomarker PENK and compare it with established and novel biomarkers.